The History of the World According to Giles: 50 Years of Headlines as Seen by the 20th Century's Greatest Cartoonist - Giles (London Hamlyn, 2010)
"For over 50 years Giles documented and satirised the most momentous events in British and world history: wars, moonlandings, sporting achievements, strikes, elections, fashion trends and entertainment, they've all been subject to his wit and artistry. Now, in this special collection, you can follow the exploits of Giles' most beloved characters such as granny, the tearaway kids and Chalky during these times, and relive some of the greatest news stories from the 20th century, decade by decade, cartoon by cartoon. As a special feature, the introduction focuses on some of the famous people who have contributed forewords to his compilations over the years, including the likes of Frank Sinatra, Prince Charles, Sir John Betjeman and many more leading politicians, comedians, actors and celebrities. Guaranteed to delight his many thousands of fans, The History of the World According to Giles takes you on a funny and fascinating journey through the remarkable events that shaped the final 50 years of the last century."--Publisher's description.
Includes Illustrations and Index.
Keywords: History, Modern -- 20th century -- Humor